TRANSLATION NORMS OF NEOLOGISM IN SOCIAL MEDIA INTERFACE - Fitria Hardini; Eddy Setia; Umar Mono (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Social media interface has been translated into a variety of languages, including Indonesian. This research aims to identify dominant types of neologisms found in social media interface, describe translation procedures applied by translators in translating neologisms and translation norms in neologism translation. This research is qualitative research that was conducted by applying Newmark’s neologism typology and translation procedures (1988) and Toury’s concept of translation norms (1995). The results showed that 1) existing lexical items with new sense (words) is a type of neologism dominantly found in an interface, 2) transference, couplets and through translation are dominant procedures applied by translators which become norms in translating neologism in social media interface. It can be concluded that neologisms found in social media interface have not had equivalents in Indonesian and neologisms cannot be translated since they are terms or jargons used in social media interface.